Detecção do risco de suicídio nos serviços de emergência psiquiátrica - Bertolote, José Manoel [UNESP]; De Mello-Santos, Carolina; Botega, Neury José (EDITORA SCIENTIFIC, 2010)
Objective: To provide guidelines for the identification of suicide risk and protective factors and the management of suicidal patients in emergency settings. Method: Literature review to identify relevant and illustrative key cases. Results: The clinical interview is the best method to evaluate the suicidal risk and has a twofold purpose: 1) providing emotional support and creating a bond; 2) collecting information. There is a substantial amount of information to be collected during the clinical interview, including risk and protective factors, epidemiologic data, characterization of the event, psychodynamic aspects, personal and family history, identification models, data on physical health, and social support network. Difficulties can emerge during the clinical interview, but a trained and informed professional will be able to approach and adequately deal with the patient. Although several scales have been proposed, none of them have shown reliable efficiency in determining the suicidal risk. Conclusion: There is no method to predict who is going to commit suicide; nevertheless, it is possible to evaluate the individual risk of each patient by means of a detailed and empathic clinical interview. Keeping the patient alive is the first and fundamental rule.
Detecting suicide risk at psychiatric emergency services